Una consideración sobre el surgimiento del Estado y los modelos consensuales. A propósito de Tiwanaku - Campagno, Marcelo (Revista Española de Antropología Americana, 2003)
Most present-day explanations about the emergence of Tiwanaku State strongly emphasize factors linked to consensus, and give little attention to those related to violence. In this article, we propose a reflection about the place occupied by material testimonies in those explanations as well as some theoretical considerations. Mainly, we sustain that, even though the testimonies linked to conflict may be scant, the process in which the State emerges can only be theoretically conceptualized if a component of violence is recognized as a basic requisite for its effective fulfillment.